Association among high blood pressure health literacy, social support and health-related quality of life among a community population with hypertension: a community-based cross-sectional study in China - Ting Chen; Wei Gan; Li Song; Yujie Wang; Huan Qi; Qinghua Zhang; Jinyu Yin (BMJ Open)
Objectives The prevalence of hypertension is increasing worldwide. Hypertensive patients in China have limited high blood pressure health literacy (HBP-HL) and social support (SS), which may have an impact on health-related quality of life (HRQoL) and lead to poorer clinical outcomes. However, the potential mechanism of HBP-HL, SS and HRQoL remains unclear. The aim of this study was to investigate the association among HBP-HL, SS and HRQoL among community patients with hypertension in China.Design A community-based cross-sectional survey.Setting The community health service center in Huzhou, China.Participants 406 community patients with hypertension were investigated from June to October 2019.Primary outcome measures HRQoL was assessed using the Quality of Life Instruments for Chronic Diseases-Hypertension V2.0, HBP-HL was assessed with the HBP-Health Literacy Scale into Chines and SS was assessed with the Social Support Rating Scale.Results Compared with moderate level of HRQoL and SS, HBP-HL of community hypertensive patients was significantly deficient. Overall, 93 patients (23.2%) lacked HBP-HL, 308 patients (76.8%) had a medium level of HBP-HL, and none of them had sufficient HBP-HL. Correlation analysis showed that HBP-HL, SS and HRQoL were positively correlated (p<0.01). The significant differences in HRQoL and SS were detected in HBP-HL level (p<0.001). In multiple linear regression models, HRQoL was significantly associated with ‘Print HL’ and ‘Medication Label’ of HBP-HL (p<0.05) and all three dimensions of SS (p<0.05). In addition, The bootstrap method was used to examine the indirect effect among variables. The results showed that SS played a mediating role between HBP-HL and HRQoL (p<0.001).Conclusion There is an association among HBP-HL, SS and HRQoL in community hypertension patients. HBP-HL can directly affect HRQoL, and through SS mediate the HRQoL. Community intervention for hypertension management should consider HBP-HL promotion and social engagement as the breakthrough points to increase the impact on patients’ HRQoL.